Playtime! : Hundreds of Creative, Easy-to-do Activities - Mason, Jane B. and Stephens, Sarah Hines; Photos by : Herring Aimee (Australia The Five Mile Press, 2009)
A great reference book from the child- development experts at Gymboree. Filled with hundreds of creative, easy to do activities such as face painting, games, dancing, party ideas, sing-alongs and crafts.
Include Color Pictures and Index
Keywords: Play -- Amusements -- Games